2006
DOI: 10.1095/biolreprod.105.049700
|View full text |Cite
|
Sign up to set email alerts
|

Global Protein Expression Profiling Underlines Reciprocal Regulation of Caveolin 1 and Endothelial Nitric Oxide Synthase Expression in Ovariectomized Sheep Uterine Artery by Estrogen/Progesterone Replacement Therapy1

Abstract: Ovariectomized (OVX) ewes were assigned to receive vehicle, progesterone (P4, 0.9-g controlled internal drug release vaginal implants), estradiol-17beta (E2, 5 microg/kg bolus + 6 microg kg(-1) day(-1)), or P4 + E2 for 10 days (n = 3/group). Uterine artery endothelial proteins were mechanically isolated on Day 10. The samples were used for protein expression profiling by the Ciphergen Proteinchip system and immunoblotting analysis of endothelial nitric oxide synthase (NOS3, also termed eNOS) and caveolin 1. Ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 43 publications
2
20
0
2
Order By: Relevance
“…In the uterine circulation, numerous studies have shown that NO produced locally by uterine artery endothelial cells (UAEC) is the most important, though not the only, factor to regulate uterine vasodilatation during normal pregnancy and the follicular phase of the estrous cycle as well as estrogen replacement therapy (Chen et al, 2006;Magness et al, 1997;Weiner et al, 1994). Uterine vasodilatation as shown by dramatic rises in uterine blood flow during pregnancy is required for delivering nutrients and oxygen to the developing fetus and thus is detrimental to fetal development (Lang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the uterine circulation, numerous studies have shown that NO produced locally by uterine artery endothelial cells (UAEC) is the most important, though not the only, factor to regulate uterine vasodilatation during normal pregnancy and the follicular phase of the estrous cycle as well as estrogen replacement therapy (Chen et al, 2006;Magness et al, 1997;Weiner et al, 1994). Uterine vasodilatation as shown by dramatic rises in uterine blood flow during pregnancy is required for delivering nutrients and oxygen to the developing fetus and thus is detrimental to fetal development (Lang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies have also demonstrated that the expression level of NOS3 gene can be up-regulated by many physiological and pathophysiological factors, including estrogen (Chen et al, 2006;Weiner et al, 1994;Zheng et al, 2005), growth factors (Inoue et al, 1995;Zheng et al, 1999), shear stress (Li et al, 2003), and protein kinase C activators (NavarroAntolin et al, 2000), whereas the inflammatory cytokines tumor necrosis factor-α (Yoshizumi et al, 1993) and bacterial toxin lipopolysaccharide (Schwartz et al, 1997) down-regulates the expression of this vasodilatory enzyme. The regulation of NOS3 expression in endothelial cells can take place at the levels of transcription (i.e., NOS3 promoter activity) and post-transcription (i.e., mRNA stability) (Fleming and Busse, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nous estimons que la progestérone et l'oestradiol, ainsi que l'aldostérone, via le récepteur minéralocorticoïde, sont des joueurs clés (flèches pointillées, Figure 4). L'administration d'oestrogènes provoque une vasodilatation généralisée, une augmentation du débit cardiaque, une faible diminution de la pression artérielle et une réduction de la résistance systémique [25]. Cette situation ressemble étrangement à celle qui prévaut durant la gestation [9,26].…”
Section: Mécanismes D'adaptation Proposésunclassified
“…Cette situation ressemble étrangement à celle qui prévaut durant la gestation [9,26]. De plus, l'augmentation d'oestrogènes contribuerait à une augmentation de l'expression de la synthase endothéliale du monoxyde d'azote qui affecterait l'ensemble de la circulation sanguine [25].…”
Section: Mécanismes D'adaptation Proposésunclassified